Foundations of cryptoeconomic systems - Voshmgir, Shermin,Zargham, Michael (WU Vienna University of Economics and Business, 2020)
Blockchain networks and similar cryptoeconomic networks are systems, specifically complex systems. They are adaptive networks with multiscale spatio-temporal dynamics. Individual actions may be incentivized towards a collective goal with
https://epub.wu.ac.at/id/eprint/7782
Keywords: Graue Literatur; blockchain; bitcoin; cryptoeconomics; tokens; complex systems; system theory; systems engineering; economics; network science